Ambiguity and vagueness in the definition of teachers’ beliefs - Hidalgo-Burneo, Diego (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
Confusion, lack of clarity or lack of consensus are the main qualifications used by those who have dealt with the conceptualization problems of teachers’ beliefs. It has even been claimed that after almost seven decades we still do not know what we talk about when refer to beliefs. Therefore, the aim of this study is to identify the central ideas contained within the definitions provided in this field since 2009. To achieve this, 102 articles published both in Spanish and in English have been reviewed. It is concluded that the term ‘belief’ is either used colloquially, i.e. as an assent, conformity or credit given to something, in which case a ‘belief’ would be what teachers express when they answer questions such as what do you believe (think, consider, etc.) about…? or that, instead of confusion, lack of clarity or lack of consensus, it would be more appropriate to talk about ambiguity and vagueness in the definitions.